2018
DOI: 10.1103/physrevlett.121.236802
|View full text |Cite
|
Sign up to set email alerts
|

Decoupling Carrier Concentration and Electron-Phonon Coupling in Oxide Heterostructures Observed with Resonant Inelastic X-Ray Scattering

Abstract: We report the observation of multiple phonon satellite features in ultra thin superlattices of form nSrIrO3/mSrTiO3 using resonant inelastic x-ray scattering. As the values of n and m vary the energy loss spectra show a systematic evolution in the relative intensity of the phonon satellites. Using a closed-form solution for the RIXS cross section, we extract the variation in the electronphonon coupling strength as a function of n and m. Combined with the negligible carrier doping into the SrTiO3 layers, these … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 68 publications
2
33
1
Order By: Relevance
“…However, a single Lorentzian did not give a satisfactory fit to the data; two Lorentzians of equal width separated by 0.25 eV were required. From the fit, we find that Γ = 0.235(4) eV, which is in good agreement with previous experimental estimates at the oxygen Kedge [10]. We note, however, that it is significantly larger than theoretical values [45,[47][48][49].…”
Section: Theory Of Epcsupporting
confidence: 90%
“…However, a single Lorentzian did not give a satisfactory fit to the data; two Lorentzians of equal width separated by 0.25 eV were required. From the fit, we find that Γ = 0.235(4) eV, which is in good agreement with previous experimental estimates at the oxygen Kedge [10]. We note, however, that it is significantly larger than theoretical values [45,[47][48][49].…”
Section: Theory Of Epcsupporting
confidence: 90%
“…Reflectively measurements and SL peaks confirm the B -site ordering and lack of stacking faults. Previous measurements of the heterostructures studied here have shown no appreciable deviation of the Ti valance from its 4 + state in bulk STO 40,44,45 . The STO layers in n SIO/1STO are consequently expected to have a negligible contribution to the magnetism studied here, although such effects have been discussed in other heterostructures 4648 .…”
Section: Methodscontrasting
confidence: 46%
“…Electron–phonon coupling has been estimated from experimental RIXS data on strongly correlated materials using the Ament model when the time scale of the phonon mode is much shorter than the core‐hole lifetime. [ 19–21 ] In our case, the CN stretching mode (190 meV, corresponding to ≈22 fs) is slightly larger than the core‐hole lifetime broadening at the N 1s (100–130 meV, ≈30–40 fs) [ 36,37 ] therefore this procedure cannot be applied. [ 22 ] Furthermore, Geondzhian and Gilmore recently suggested that RIXS may rather be probing exciton–phonon coupling when the core‐hole is not well screened, [ 38 ] which is likely to be the case for PCN.…”
Section: Resultsmentioning
confidence: 99%
“…Over the last years, the development of high‐resolution RIXS has enabled the observation of vibrational structures in the quasi‐elastic part of RIXS spectra opening new insights into ultrafast molecular dynamics [ 18 ] and vibronic coupling in solid materials. [ 19–22 ] Nevertheless, RIXS has not been applied to PCN so far to our knowledge.…”
Section: Introductionmentioning
confidence: 99%